(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the epidemiological profile of tuberculosis in the city of Recife from 2015 to 2020. Methodology: This is a retrospective, descriptive study with a quantitative approach on the epidemiological profile of tuberculosis cases in the city of Recife from 2015 to 2020, with data collected in the Notifiable Diseases Notification System from December 2021 to January 2022. Results: There were 15,181 cases of tuberculosis reported in the city of Recife during the study period, with a predominance of males (68.1% ), age group 20-39 (42.85%), with the clinical pulmonary form in evidence (79.4%), with the majority of the entry mode being new cases (71.9%) and with leaving tuberculosis as a cure (47.6%). The relationship of tuberculosis with other pathologies and social conditions of those affected was quite evident. Conclusion: It was evident that tuberculosis is still quite present in the city, health education actions and combating abandonment are important to reduce its prevalence.